Production ecology of Brassica Juncea (L.) czern. var. ensabi / Abbas Falah Toosi - Toosi, Abbas Falah (2010)
The Malaysian brassica (B. juncea var. Ensabi) with its distinct pungent aroma and bitter taste is now cultivated as a local plant among the Malays and natives of Sabah and Sarawak. The species is also used as a popular kimchi by the locals.Experiments were conducted to determine the effect of light, temperature regimes, salinity, drought stress and chemical media on seed germination and to assess clonal growth, structural demography and general growth patterns of B. juncea var.Ensabi. Fertilizer requirements, self-thinning, inter-plant spacing, assessment of the chemical nature and allelopathy activity of B. juncea var. Ensabi were also investigated in this study. Seeds of B. juncea var. Ensabi were collected from Kuching, Sarawak. Most complete germination occurred at 25o-30oC and these were optimum for germination percentage and 30oC was the best temperature for rate of germination for oven-dried seeds. No seed germination prevailed when exposed to chemical media. The hypocotyl indicated the optimum length growth was 22.8 mm at 25oC on dry seeds under total darkness and for fresh seeds under same conditions was 23.7 mm at 25oC. Light regime strongly influenced clonal growth of B. juncea var. Ensabi. Yield and yield components of B. juncea var. Ensabi increased as the proportion of fertilizer increased from 0 to 150 kg of the total NPK plus 150 kg Nha-1 supplied more than farmers experience used. Based on these results N application higher than optimal rate had adverse effect on yield of B. juncea var. Ensabi. Intra-specific competition had a profound effect on the number of individuals in a population, as illustrated by the Log of average leaf weight per plant plotted against xxvii the log of density of survivors for a plant population. The leaf population's trajectory was held under a line of slope -1.29 (R2 = 0.63, p<0.05). The effect of inter-plant spacing on the growth of individual plants in an increased space and with equal sample size (number of plants) for each spacing gradient was investigated under varying plant spacing. The experimental design consisted of plants positioned in a polar coordinate grid with seven arcs, eighteen rays and an angle of 20o. The distance between arcs increased exponentially from 6 cm to 43 cm. Rays were separated by an angle of 20o. B. juncea var. Ensabi showed very high survival percentages even when planted at high densities for a period of 100 days after planting. Widely-spaced plants were significantly taller than the more closely spaced plants of the same cohort. Mean stem diameter, plant biomass, number of leaves and branches and pod/plant increased with plant (wider) spacing. These results support the concept of competition in the self-thinning rule. Oil concentrations of the B. juncea var. Ensabi seeds was 34.6% and the protein concentration of the Ensabi seeds was 32.1%. The fatty acid profile of Ensabi showed on average oleic acid (C18:1) concentration in the oil produced from B. juncea var. Ensabi was 18.2% whereas the concentration of other fatty acids were: linoleic acid (16.9%), linolenic acid (5.5 %), eicosenoic acid (8.8%), erucic acid (42.0%), stearic acid (1.4%), and palmitic acid (2.5%), which was the major present as the major component.In the study of allelopathy, aqueous extracts from fresh materials were assayed with concentrations of 0, 50, 100, 150, 200 and 300 g L-1. The parallel concentrations of aqueous extracts of oven-dried materials used were 40, 80, 120, 160, 200 and 300 g/L. Inhibition of seed germination of radish prevailed at concentrations above 200 and 300 gL-1 of the aqueous extract of dried materials, while with ethanol extract similar inhibitions were observed at concentrations range of 14.28 − 30 gL-1. Total inhibition of root and shoot growth was also observed in barnyard grass. Both species were susceptible to plant extracts isolated from leaf, stem and root of B. juncea var. Ensabi. Root and shoot lengths of radish and barnyard grass were decreased with the extracts. Results are discussed from the viewpoint of possible use of the extracts as a natural herbicide to control barnyard grass and other susceptible weed species.